Acquisire e insegnare l’italiano in un contesto minoritario: L’esempio delle valli ladine - Videsott, Ruth (Incontri. Rivista europea di studi italiani, 2022)
Learning and teaching Italian in a minority context: the example of the Ladin valleys This paper aims at reflecting on the acquisition and teaching of Italian as a second language in the minority context of the Ladin valleys in South Tyrol. Since this area is characterized by a historical multilingualism and consequently by an important presence of Italian and German, Ladin children grow up in a multilingual setting, where Italian can be L1 or is learned through the social and institutional context as L2. Moving from the project AcuiLad, which examines first and multilingual acquisition processes at kindergarten age in the Ladin valleys in South Tyrol, four case studies of Italian conversations by Ladin children aged 3 to 6 will be presented. This analysis shows that the main morphological characteristics of Italian are acquired before entering school. The interference of the L1, Ladin in this case, can be mostly observed on the lexical level and in minor way on the morphological one. In terms of language teaching, this could mean in Ladin schools more situations of integrated linguistic education could be foreseen, especially for grammatical contents, since the grammatical competences are more or less the same for Italian, German and Ladin.